Acupuncture-assisted anaesthesia for catheter ablation of atrial fibrillation to reduce the consumption of morphine hydrochloride and postoperative nausea and vomiting (PONV): study protocol for a randomised controlled trial. Issue 12 (15th December 2022) - Zhang, Xuecheng; Wang, Qi; Dong, Yujiang; Jia, Yuqi; Hou, Zhihui; Deng, Wenqi; Zhang, Menghe; Mu, Qiurun; Jia, Hongling
Abstract : Background: Patients often experience postoperative nausea and vomiting (PONV) after catheter ablation of atrial fibrillation (AF) because of the use of opioids for anaesthesia and analgesia during the procedure. Some clinical trials have demonstrated that acupuncture-assisted anaesthesia (AAA) reduces opioid consumption and prevents PONV. Although several studies have been conducted on AAA, its safety and efficacy in AF catheter ablation remain unclear due to small sample sizes and a paucity of methodologically rigorous designs. Therefore, this trial was designed to evaluate the safety and efficacy of AAA in reducing PONV and morphine hydrochloride consumption during catheter ablation. Methods: This single-centre, patient-blinded, randomised, non-penetrating sham-controlled trial will be conducted in China. A total of 100 patients will be randomly assigned to the AAA and conventional anaesthesia (CA) groups in a ratio of 1:1. The patients will receive AAA or CA plus sham acupuncture during catheter ablation and will be followed up for 30 days. The primary outcomes include the total amount of morphine hydrochloride consumed during catheter ablation and PONV within the first 24 hours after the procedure. The secondary outcomes include pain, nausea and vomiting, anxiety, patient's ability to cope during catheter ablation, AF recurrence and quality of life, as assessed using the numeric rating scale. Adverse events will be recorded and their influence will be analysed at the end of the trial. Discussion: This study will help in evaluating the safety and efficacy of AAA applied for AF catheter ablation in reducing opioid doses during the procedure and the occurrence of PONV. Ethics and dissemination: The study has been approved by the Medical Ethics Committee of Second Affiliated Hospital of Shandong University of Traditional Chinese Medicine. The results of the study will be published in peer-reviewed journals and presented at conferences if possible. Trial registration number: ChiCTR 2100042646; Chinese Clinical Trial Registry.